Transmissão vertical, resistência aos antirretrovirais e diversidade genética do HIV-1 em gestantes infectadas do Centro-Oeste do Brasil - Lima, Yanna Andressa Ramos de (2014)
HIV-1 mother-to-child-transmission (MTCT) is a multifactorial event associated mainly with maternal viral load. Thus, the molecular epidemiology of HIV-1 and the evaluation of factors associated with MTCT in pregnant women are crucial for epidemic understanding and monitoring in this population. Objectives: To assess the frequency of recent seroconversion cases among newly diagnosed, antiretroviral (ARV) naïve pregnant women and evaluation of pregnancy outcomes and transmitted drug resistance (TDR) in this group; to compare sociodemographical, clinical, genetic diversity of the virus and resistance among young and adult pregnant women. Methods: HIV-1-infected pregnant women (n = 250) were recruited during antenatal care conducted by the Program for the Protection of Pregnant Women from Goias State (PPPW/GO). Recent cases of seroconversion were identified by BED-CEIA among naïve pregnant women and confirmed by ambiguous nucleotide calls. Pol gene (protease/PR and 2/3 of the reverse transcriptase/RT) was sequenced from plasma samples. Resistance mutations were evaluated by Calibrated Population Resistance tool and Stanford HIV-1 and International AIDS Society-USA (IAS-USA) databases. Viral subtypes were assigned by REGA software and phylogenetic analyzes with reference sequences. Results: Cases of recent seroconversion (RS) were identified in 16.6% of 95 newly diagnosed, ARV-naïve pregnant women. Medians of CD4+ cell count and viral load were 530 cells/μL and 8,796.5 copies/mL, respectively. Nine patients with RS probably seroconverted during pregnancy. One case of MTCT was observed among pregnant women with RS. Incident cases presented a predominance of isolates assigned as subtype B. There was no difference regarding the distribution of non-B subtypes. The amont of 250 pregnant women recruited were divided into two distinct age groups: adolescents and young (96/250, 38%) and adult women (154/250, 62%). When compared with the adult group, young women had fewer previous pregnancies and they were diagnosed mainly in the current pregnancy. One case of MTCT was identified in both groups (2/250, 0.8%). The CD4+ cell counts were similar between both groups. Viral load was significantly higher among ARV-naïve pregnant adolescents (15-19 years) when compared with the group of ARV-naïve pregnant adults (>24 years). Young pregnant women previously exposed to ARVs were less likely to have viral load <1,500 copies / mL. The distribution of HIV-1 subtypes was similar in both groups and recombinant subtypes with similar recombination points were identified among both groups. The frequency of transmitted resistance was similar between young and adult women (9.5% and 7.1%, respectively). The frequency of secondary resistance was higher among adult pregnant women compared with younger women (21.8% and 12.8%, respectively). Conclusions: Recent seroconversion during pregnancy associated with moderate levels of transmitted resistance may contribute to vertical transmission of HIV-1. Preventive measures should include adolescents and young women as an attempt to control the vertical transmission of HIV-1 in Central Western region, Brazil.